How and When do Psychological Contract and Justice Perceptions Affect the Relationship between Servant Leadership and Employee Work Outcomes? - Bibi, Annam (UI Scholars Hub, 2022)
Academicians and practitioners have always been equally attracted to learning the effects of varied leadership styles on employee work outcomes. This study examines how servant leadership influences employee behaviors (organizational commitment, organizational citizenship behavior, and employee engagement) and evaluates the roles discharged by psychological contract and organizational justice perceptions on these relationships. Data were collected from 168 employees working in public hospitals. A standardized questionnaire was used to gather the data. Hypotheses were tested through hierarchical regression analyses. The study results revealed that servant leadership is positively associated with organizational commitment, organizational citizenship behavior, and employee engagement. Psychological contract partially mediates the effects of servant leadership on organizational commitment, organizational citizenship behavior, and employee engagement. Further, organizational justice perceptions moderate the associations between servant leadership and employee behaviors. The study results contribute to the extant research evidencing that servant leadership exerts direct as well as mediating effects on employee attitudes and behaviors. This study intensifies the comprehension of the impact of servant leadership on employee workplace outcomes. A superior understanding of the influence of leadership on a wide variety of employee attitudes and behaviors could inform solutions that better address demands for more people-centered management, caring leadership styles, and concern for the success of all organizational stakeholders.